Pengaruh Pelvic Rocking Exercise Terhadap Kemajuan Persalinan Kala 1 Fase Aktif - Yuli Susanti, Neny; Nikmah, Nurun; Watna, Ida (Universitas Muhammadiyah Gresik, 2025)
Background : The high maternal mortality rate is partly related to prolonged labor (4.3%).Pelvic rocking exerciseor pelvic rocking exercises can help give birth more quickly by preparing the pelvis to relax and open more easily during contractions by rocking and rocking it back and forth, right and left, and in a circular motion. Objective : This study aims to determine the effect of pelvic rocking exercise on the progress of labor in the first active phase at Banyuputih Health Center, Situbondo. Method : This study was a quasi-experimental study. Pregnant women in their third trimester were randomly selected using purposive sampling and then taught pelvic rocking exercises. During labor, the duration of the active phase was observed using observation sheets and a partograph. Data were analyzed using univariate, bivariate, and multivariate analyses. Results :Research resultshows that pelvic rocking exercise increases the efficiency of the first stage of the active phase in mothers giving birth with a p-value of 0.024 which is smaller than the significance level of α = 0.05, meaning that PRE affects the length of the first stage of the active phase of labor. Conclusion : The influence of pelvic rocking exercise on the progress of labor in the first active phase.